Avaliação em edifício escolar: segurança contra incêndios - APAE - Meira, Francieli Aparecida (2014)
This study has an objective to develop an Assessment in a schoolbuilding APAE (AssociationofParentsandFriendsofExceptionals) of Pato Branco, focusingonfiresafety installations and panic. The methodology used in this study was based on the theoretical assumptions of post-occupancy evaluation and assessment methods for technical and constructive type for fire safety. The survey was developed through technical visits and iconographic record aiming to raise and assess the equipment and systems at the existing building to prevent and combat on fire . For the evaluation were used security parameters required by the Fire Department of the State of Paraná . As a tool for preparing proposals for adaptation and improvement of the overall system of prevention and firefighting and panic, it was used the method of matrix performance in which was defined the degree of importance and the degree of compliance with the requirements of legislation for each variable system . As a result of this research, it denotes the preventive survey through the building floor plan, verification and analysis of care standards requirements. The evaluation is that a system of fire safety and handicapped panic is important in case of a claim for both users of the building, and workers in particular since many students have difficulties in walking; and as well as to all the physical assets of plant and equipment.